Pengembangan Orientasi Keterampilan Abad 21 pada Pembelajaran Fisika melalui Pembelajaran PjBL-STEAM Berbantuan Spectra-Plus - Sri Lestari (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2021)
This study aims to describe the development of 21st century skills with spectra-plus-assisted STEAM-based PjBL learning on the main material of sound waves in musical instrument prototypes.This type of research is a type of research and development (R & D) with a sample of 32 class XI MIPA 2 students in SMA Negeri 1 Yogyakarta Semester 2 of the 2019/2020 academic year. To determine the increase in scientific critical thinking skills after spectra-plus-assisted STEAM-based PjBL learning using normalized gain. Meanwhile, to determine the ability of creative skills, communication and collaboration using questionnaires and observation sheets.The results showed that there was an increase in scientific critical thinking skills, normalized gain score of 0.54 and creative thinking, normalized gain score of 0.65 after implementing PjBL learning based on spectra-plus assisted STEAM in the moderate category. From the results of the observation sheet, the average collaboration ability is 73% in the high category and the average communication ability is 77% with the high category. The response of students to the application of STEM-based PjBL was 78.21%. Student responses were quite positive towards the application of STEAM-based PjBL in learning. From the results of data processing and discussion, it can be concluded that learning with the STEAM method (Science, Technology, Engineering, Art and Mathematic) by linking science (science), technology, engineering, art, and mathematics can develop soft skills because students are given comprehensive understanding of the interconnectedness of disciplines through 21st century skills learning experiences.